Student’s attitude toward foreign language learning - Noroña Heredia, Mayra Clemencia (2022)
The Research Project entitled: "STUDENTS' ATTITUDE TOWARD FOREIGN LANGUAGE LEARNING'' aimed to identify how students' attitudes impact foreign language learning at the Centro de Idiomas of Universidad Técnica de Cotopaxi (CI-UTC) from social and psychological perspectives. The methodology used in this research is exploratory because it is based on examining information with greater precision on previously investigated topics. Also, the survey method was used during the literature review to acquire precise results, existing knowledge, and notions to develop this research, this test tool used for evaluate the attitudes is a questionnaire by Gardner (1985). The methodology is quantitative because a survey-based questionnaire was applied during the research. The results were tabulated and divided into five constructs: integrativeness, language learning process, motivation, anxiety toward English language, and instrumental orientation.